You are on page 1of 7

Samy Abdallah v-21245499

1er examen
3)
4

a ¿∫
1

Solución
1

∫ √x
1

∫ √x
1

∫ √x

dx -

∫ 1 dx

dx =

2 √x

dx

−1

∫x 2
−1

+1

x2
−1
+1
2
2

√x

∫ 1 dx
X

2

√x

–x+C

lim ( 2 √ x – x )
x→ 1

=1

( √1x −1) dx

√1

2

– 1= 1

lim ( 2 √ x – x )

=0

x→4

0 – 1 = -1

3

c ¿ ∫ √|x|−x dx
−2

Solución
0

3

∫ √(−x )−x dx+∫ √ x−x dx
0

−2
0

∫ √(−x )−x dx
−2

=

3

∫ √ x−x dx
0

8+0=8

=0

8
3

2do examen
3)

a ¿∫

x2
3
2 2

( 16−x )
U=

x2

U´= 2x

1
V´=

3

(16−x2 ) 2
x

V=

64 1−

x2
16

x
x2

64 1−

x2
16

dx
-

∫2 x

x

64 1−

x2
16

dx

dx

x

3

64 1−

x2
16

-

x2

x2 =
32 1−
16

1

32

2

x

32 1−

x
4
( ¿)
seno−1 ¿

x2

1−

x2
16

1 64 sin u cos u
du
32 ∫ √ 1−sen 2 u
1
sin u cos u
64
du
32 ∫ √ 1−sen2 u
1
cos u sen2 u
64∫
du
32
√ cos 2 u
1
cos u sen2 u
64∫
du
32
cos u
1
64∫ sen 2 u du
32
1
1−cos 2 u
64∫
du
32
2
1
1
64 ∫ 1−cos 2 u du
32 2
1 du−¿ ∫ cos 2 u du
1
1
64 ∫ ¿
32 2

∫ 1 du=u

x2
16

1
2

−1

seno (2 seno

x
4 )

1

∫ cos 2 u du= 2

seno 2u

(

1
1
1
−1 1
−1 1
64 sin
x− seno 2 sin
x
32 2
4
2
4

(

))

x
4

2sin −1

)
x 1
sin −1 − sen ¿
4 2
−1

sin

x
4

x3

64 1−
x

x2
16

3
2

x
64 1−
16

−¿

1
x
sen (2 sin−1 ) ¿
2
4

-

−sin −1

x
4

+

1
x
sen (2 sin−1 )¿
2
4

x

b ¿∫ e senx dx

Solución
e

U=

x

e

U´=

x

V´= seno x
V= - cosx

ex

(- cos x ) -

∫ e x (−cosx ) dx

x−¿∫ −e x cos x dx
−e x cos ¿
e x cos x dx
−¿∫ ¿
x−¿
−e x cos ¿

e

U=
U´=

x

e

x

V´= cos x
V= sin x
- e

x

x dx
cos x – ( - ( x e sin¿
e sin x −∫ ¿ ¿¿
x

1

- 2e

x

( cos x – sen x )

1 x
e (cos x – sin x) + C
2

-

8+ 4 x−x 2
∫ x 3 +8 dx

c.)

solución:

¿∫

8
4x
x2
dx+
dx−
dx


x 3 +8
x 3+ 8
x 3 +8

∫ x38+ 8 dx=8

( (√

∫ x43 +x8 dx=4

((

1
12

1
6

3 arctan

√3 arctan

( x√−13 )− 12 ln|13 ( x−1) +1|)+ 121 ln|x+ 2|)
2

1
1
+ ln |( x−1 ) +3| + ln |x +2|
( x−1
)
)6 )
√3 2
2

x2
∫ x3 + 8 dx= 13 ln| x3 +8|
=

8

( (√
1
12

3 arctan

1 1
1
1
x−1 1
1
− ln| ( x−1 ) + 1| + ln |x +2| +4
+ ln|( x −1 ) +3| + ln |x+ 2
√ 3 arctan (
( x−1
)
)
)
(
)
2
3
12
)
(
6
2
6
√3
√3
2

2